Systematic review and narrative synthesis of pharmacist provided medicines optimisation services in care homes for older people to inform the development of a generic training or accreditation process. (12th November 2019) - Wright, David John; Maskrey, Vivienne; Blyth, Annie; Norris, Nigel; Alldred, David P.; Bond, Christine M.; Desborough, James; Hughes, Carmel M.; Holland, Richard Charles
Abstract: Objectives: To develop a training programme to enable pharmacists with prescribing rights to assume responsibility for the provision of pharmaceutical care within care homes, a systematic review and narrative synthesis was undertaken to identify reported approaches to training pharmacists and use this literature to identify potential knowledge requirements. Methods: A PROSPERO‐registered systematic review was performed using key search terms for care homes, pharmacist, education, training and pharmaceutical care. Papers reporting primary research focussed on care of the older person within the care home setting were included. No restrictions were placed on methodology. Two researchers independently reviewed titles, abstracts and papers. Agreement on inclusion was reached through consensus. Data on titles, training and activities undertaken were extracted and knowledge requirements identified. Findings were synthesised and reported narratively. Key findings: Fifty‐nine papers were included, most of which were uncontrolled service evaluations. Four papers reported an accreditation process for the pharmacist. Thirteen papers reported providing tools or specific training on a single topic to pharmacists. The main clinical and therapeutic areas of activity (requiring codified knowledge) were dementia, pain, antipsychotic and cardiovascular medication. Provision of pharmaceutical care, effective multidisciplinary working and care home staff training represented the main areas of practical knowledge. Conclusions: Information regarding training and accreditation processes for care home pharmacists is limited. This study provides insight into potential codified and practical knowledge requirements for pharmacists assuming responsibility for the provision of pharmaceutical care within care homes. Further work involving stakeholders is required to identify the cultural knowledge requirements and to develop a training and accreditation process.